Credit Risk Assessment in the Romanian Banking System. Evidence from the Recent Financial Crisis - Anamaria Avadanei (CES Working Papers, 2011)
The financial crisis followed by the recession has adversely affected the quality of Romanian banking assets. The aim of this paper is to point out the implications of credit risk in the Romanian banking system following the accelerate dynamics of credit activity before the financial crisis and the effects vs. solutions proposed and implemented in recent years. Structured on four parts, the study presents the recent contributions in the crisis-lending relationship, the main features of the Romanian banking system, the evaluation of credit risk in terms of numbers, facts, actions and a short analysis of the correlation between credit indicators (consumer credit, credit risk ratio, medium exchange rate and the number of employees in the economy). To conclude, we propose to define the key points of the future Romanian banking activity.
Keywords: G01; G21; G32; 330; credit risk; financial crisis; Romanian banking system Romania